Housing Needs of Asset-Poor Older Australians: Other Countries' Policy Initiatives and Thier Implications for Australia - Ong, R; Colic-Peisker, V; Bailey, N; Berry, M; Wood, G (My University, 2010)
This Positioning Paper is the first output of a project that explores housing options and actual housing circumstances of asset-poor older Australians.
Australian Housing and Urban Research Institute Positioning Paper
Keywords: Housing; Housing, communities and neighbourhoods; Housing; Housing, community and neighbourhoods